2023
DOI: 10.1088/1741-4326/accdec
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of core MHD events in thousand-second improved confinement plasma on the EAST tokamak

Abstract: Recently, stationary plasma with a world-record pulse length of 1056 s was realised on the Experimental Advanced Superconducting Tokamak (EAST). In this work, the core magnetohydrodynamics events and the mode coupling process were investigated during EAST long pulse operation with dominant electron heating, pure radio frequency wave heating, and low collisionality by using several diagnostics and the nonlinear numerical code M3D. A saturated m/n=1/1 kink mode was observed in the core region, where a stable int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…This study concentrates on the formation and long-sustention of ITB in EAST discharges with lower hybrid wave (LHW) and electron cyclotron radio heating (ECRH). Characterized by dominant electron heating and minimal torque input, these discharges closely mimic the conditions anticipated in future reactors [2,3]. Recent experiments in the AUG tokamak have illustrated that the presence of fast particles can induce robust, axisymmetric E × B flows, playing a pivotal role in ITB formation [4].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…This study concentrates on the formation and long-sustention of ITB in EAST discharges with lower hybrid wave (LHW) and electron cyclotron radio heating (ECRH). Characterized by dominant electron heating and minimal torque input, these discharges closely mimic the conditions anticipated in future reactors [2,3]. Recent experiments in the AUG tokamak have illustrated that the presence of fast particles can induce robust, axisymmetric E × B flows, playing a pivotal role in ITB formation [4].…”
Section: Introductionmentioning
confidence: 69%
“…Milder m/n = 1/1 modes with higher frequencies and smaller amplitudes are better to confine fast electrons (energy < 50 keV). Frequency chirping in these m/n = 1/1 modes can reach up to 80%, primarily due to variations in local diamagnetic drift velocity [2]. The generation of super-fast electrons has the capability to drive non-inductive current and alter V loop , with a maximal V loop shift recorded at approximately 20 mV at t = 24.8 s. The contribution of fast electrons to plasma pressure aligns with the predictions made by CQL3D, as delineated in figure 9.…”
Section: Saturation Mechanism Of the M/n = 1/1 Modementioning
confidence: 99%
See 1 more Smart Citation
“…The causes for the generation of TMs in EAST are diverse and complex. For example, it has been observed that m/n = 2/1 TM [27] and 3/2 TM [28] are triggered by the strongly coupled m/n = 1/1 internal mode, and m/n = 2/2 sawtooth mode and its higher-order harmonic mode excite m/n = 3/2 TM. Generally, the m/n = 3/2 TM and m/n = 2/1 TM are characterized by the formation of magnetic islands on q = 1.5 and q = 2 rational magnetic surfaces, respectively.…”
Section: Three Mhd Modes On Eastmentioning
confidence: 99%